1995
DOI: 10.1002/bip.360350502
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of methylene blue, azure B, and thionine with DNA: Formation of complexes with polynucleotides and mononucleotides as model systems

Abstract: University of Dublin Dublin 2The interactions of methylene blue, azure B, and thionine with calf thymus DNA, [poly (dG-dC)12, [poly(dA-dT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 50 publications
7
86
1
1
Order By: Relevance
“…No significant differences were observed between the 1-h and 16-h drug incubations, suggesting that the drug localizes rapidly in the nuclear region of the cells -an observation that broadly agrees with the limited microscopy evidence obtained in this study and with literature evidence. Methylene blue and other dyes of this structure have been reported to intercalate rapidly into DNA, binding predominantly to purine nucleotides (Tuite and Kelly, 1995). However, in our study, no residual DNA damage in MB-PDT-treated cells was observed after 4 hours' repair.…”
Section: Dna Damagecontrasting
confidence: 61%
“…No significant differences were observed between the 1-h and 16-h drug incubations, suggesting that the drug localizes rapidly in the nuclear region of the cells -an observation that broadly agrees with the limited microscopy evidence obtained in this study and with literature evidence. Methylene blue and other dyes of this structure have been reported to intercalate rapidly into DNA, binding predominantly to purine nucleotides (Tuite and Kelly, 1995). However, in our study, no residual DNA damage in MB-PDT-treated cells was observed after 4 hours' repair.…”
Section: Dna Damagecontrasting
confidence: 61%
“…1.85 × 10 5 M −1 , which is comparable to the affinity of phenothiazine dyes for DNA. 36 Notably this is an order of magnitude higher than that seen for the unsubstituted analogue 2, demonstrating once more the importance of the 4-amino moiety and ICT character of 1.…”
Section: 2034mentioning
confidence: 88%
“…6a inset and Table 6), which are comparable to the affinity of phenothiazine dyes for DNA 23 and naphthalimides fused with heterocyclic rings. 24 Interestingly, the presence of the dimethyl substitution on the 4-amino nitrogen did not appear to have any significant effect on the DNA binding affinity of 3, in contrast to what was observed for the mononucleotides.…”
Section: Interaction With Salmon Testes (St)-dnamentioning
confidence: 64%